Development and evaluation of educational video on healthy maternal diet to prevent child stunting - Mohd Shukri, Nor Azwani; Norman, Muhammad Farhan Hanif; Rostam, Muhamad Ashraf; Ab Hamid, Mohd Ramadan; Abu Seman, Muhamad Sadry; Romli, Rahiwan Nazar (UMT Press, 2024)
This study aimed to develop an animated educational video on healthy dietary intake during pregnancy to prevent child stunting and evaluate its suitability, understandability, and actionability. An animated video draft on recommended maternal total energy, carbohydrate, protein, and fat intakes during pregnancy was developed based on a review of available guidelines. The video content and features were evaluated by six field experts and 33 reproductive-aged women (target viewers). The evaluation was conducted using the Suitability Assessment of Materials and Patient Education Materials Assessment Tool for Audiovisual Materials tools. The video was suitable for use, with an 85% score indicating superior content. It has acceptable levels of understandability (83%) and actionability (72%), as evaluated by experts. The improved video received better ratings of understandability (97%) and actionability (98%) from the intended viewers. The newly developed animated video on healthy maternal nutrition during pregnancy has demonstrated its acceptability among the target viewers. The video has desirable levels of suitability, understandability, and actionability and thus has the potential as a nutrition education tool to impart knowledge and increase the understanding of mothers regarding healthy dietary intakes during pregnancy to prevent further cases of child stunting in Malaysia.